Cistična degeneracija adventicije arterijske popliteje in komunikacija s kolenskim sklepom - Kozar, Franc (Zdravniški vestnik, 2006)
Background Atherosclerosis is the most common cause of lower limb ishemia in developed world. Other nonatherosclerotic causes must be considered in a youngpatient without specific risk factors, among them cystic adventitial degeneration of popliteal artery, a rare disease with unknown etiology. Patients and methods A 27 year-old male patient presented with symptoms of intermittent claudication. He had no risk factors. After prompt diagnosis a surgical procedure was performed .A cystic formation was found in popliteal artery which communicated with knee joint. We evacuated the cyst and closed the communication with the joint. Patient is symptom free at the moment. Conclusions When dealing with a younger patient with signs of intermittent claudication, we have to consider nonatherosclerotic causes of disease, among them cystic adventitial degeneration of popliteal artery. Therapy is surgical,obtained results are very good without recurrence of cysts.
Keywords: Adult; arterije; Ciste; cistična degeneracija; Cysts; diagnostika; etiologija; Intermitetna klavdikacija; Intermittent Claudication; Knee Joint; Kolenski sklep; Odrasli; ožilje; Pathology; Popliteal Artery; Poplitealna arterija; Surgery